(untitled) (Numerus academy review, 2026)
The study aims to investigate the poem of the national anthem according to the perspective of the textual linguistic approach, which is based in its analysis of the texts on identifying the tools and mechanisms that ensure the text’s verbal continuity and semantic coherence, by standing on the manifestations of its consistency and coherence factors; The study takes the Algerian national anthem as an applied field, limited to determining the manifestations of textual consistency in the poem, which we summarize in reference, replacement, deletion, kindness and lexical consistency. and if so; What are the mechanisms and means used by the poet "Mofdi Zakaria" to achieve this textual interconnection? What is the role of these mechanisms in understanding the significance of the poetic poem? In order to confront these questions and analyze this poetic discourse in a textual and linguistic way; I employed the descriptive approach with activating the mechanisms of analysis.